MATHEMATICAL MODELING AND THERMAL ANALYSIS OF A THERMOELECTRIC COOLER BOX USING A WATER-COOLING BLOCK AND HEATSINK–FAN SYSTEM - I Nyoman Agus Adi Saputra; Adi Winarta; I Wayan Sutina (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
This study presents a mathematical modeling and thermal performance analysis of a Thermoelectric Cooler Box (TEC) equipped with two hot-side heat rejection systems: a Water Cooling Block (WCB) and a Heatsink–Fan (HSF). Thermoelectric cooling offers an environmentally friendly alternative to vapor-compression refrigeration because it operates without refrigerants and requires only low-voltage DC power. The objective of this work is to evaluate the influence of electrical current on temperature distribution, cooling capacity (Qc), and the coefficient of performance (COP) of a TEC1-12706 module under both cooling configurations. The mathematical model is formulated based on the energy balance between the cold and hot sides, incorporating the Peltier effect, thermal conduction, and Joule heating losses. Numerical simulations were performed in Python for currents ranging from 1 to 7 A. The results show that the WCB reduces the hot-side temperature (Tₕ) by 6–8 °C compared with the HSF, indicating superior heat rejection. However, the HSF system achieves a slightly higher COP (about 5–7%) due to the lower cold-side temperature (Tc) obtained in the WCB configuration, which reduces the effective Peltier cooling term. The maximum COP for both systems occurs at 3–4 A, corresponding to a temperature difference (ΔT) of approximately 28 °C. Although the cooling capacity of the WCB is slightly lower (<10%) due to increased back-conduction, it offers better thermal stability and long-term performance consistency. Overall, the developed mathematical model accurately represents the TEC’s thermal behavior and provides a reliable foundation for optimizing water-cooled thermoelectric designs.